Stability and ORR performance of a well-defined bimetallic Ag70Pt30/Pt(111) monolayer surface alloy electrode – Probing the de-alloying at an atomic scale. (1st January 2018) - Beckord, S.; Brimaud, S.; Behm, R.J.
Abstract: Aiming at a better understanding of surface de-alloying processes on an atomic scale and its impact on the electrocatalytic properties of bimetallic electrodes in the oxygen reduction reaction (ORR), we have investigated the electrochemical de-alloying of a Ag70 Pt30 monolayer surface alloy on Pt(111), in electrochemical potential step measurements and the performance of the resulting electrodes in the ORR. Structurally well-defined electrode surfaces were prepared and characterized by scanning tunneling microscopy (STM) before and after the electrochemical (EC) measurements under ultrahigh vacuum (UHV) conditions. Potential step experiments were performed in a dual thin-layer flow cell in 0.5 M H2 SO4 supporting electrolyte, using a UHV-EC transfer system which allowed electrode transfer without intermediate contact to air. STM imaging reveals an increasing, selective removal of Ag from the surface layer in the potential range 0.95–1.05 VRHE, resulting in the formation of monolayer vacancy islands. The last 10% of Ag were removed only at the onset of Pt corrosion and 3D surface restructuring at 1.10 VRHE . Correlating these findings with the total amount of dissolved Ag determined in electrochemical measurements we propose a possible corrosion mechanism. The corroded surfaces, in particular the more strongly corroded surfaces, showed an improved ORR performance, with a lower overpotential, by up to 100 mV, and a lower H2 O2 yield than Pt(111). The higher stability of the surface alloys compared to a Ag(111) as well as the ORR activity are discussed in terms of electronic ligand and strain effects, for the latter structural effect have to be considered as well. Graphical abstract: Highlights: Preparation of structurally well-defined Ag70 Pt30 /Pt(111) surface alloy electrodes. Surface de-alloying of Ag70 Pt30 /Pt(111) monolayer surface alloy on an atomic scale. Potential dependent change from 2D surface dissolution to 3D restructuring. Ag surface atoms with different stability towards electrochemical corrosion. Improved ORR performance of the corroded electrodes compared to Pt(111).